Epilobium montanum L. in E. collinum C. C. Gmel. v Sloveniji - Strgulc-Krajšek, Simona (Hladnikia (Ljubljana), 2001)
The article discusses taxa Epilobium montanum and E. collinum in Slovenia. After morphometric analyses several distinguishing characters were found, someof them already stated in the older literature. After revision of herbarium material distribution maps were made.
Keywords: botanika; Classification; Ecosystem; Ekosistem; fitogeografija; Plants; Rastline; Rhododendron-Park Bremen; Slovenia; Slovenija; vegetacija